Effect of Biochar and Nitrogen on Growth and Yield of Shallots (Allium Ascalanicum L.) - Abdarah Abdarah; Sukartono Sukartono; Bambang Budi Santoso; IGM Kusnarta; Kisman Kisman (IKIP Mataram, 2021)
Shallots (Allium ascalanicum L.) is a vegetable commodity that has high economic value. The productivity of shallots in NTB is still relatively low because the level of soil fertility is still decreasing. One of the efforts to increase the productivity of shallots can be done through the addition of soil fertility enhancers by providing biochar and fertilization efficiency. This study aims to determine the effect of biochar, nitrogen fertilizer and interactions on the growth and yield of shallots. The experiment has been carried out since May –August 2021 at the Greenhouse of the Faculty of Agriculture, University of Mataram. The experiment was designed using a factorial Completely Randomized Design consisting of two factors, namely the dose of Biochar (4 levels) B0: 0 tons/ha without Biochar, B1: 10 tons/ha, B2: 20 tons/ha, B3: 30 tons/ha and the dose Nitrogen (5 levels) N0: 0 kg/ha without Nitrogen, N1: 200 kg/ha, N2: 400 kg/ha, N3: 600 kg/ha, N4: 800 kg/ha. The results showed that there was an interaction between the dose of biochar and nitrogen on growth (plant height, number of leaves and number of cloves) and yield (wet weight and dry weight), where doses of biochar 30 tons/ha and nitrogen 800 kg/ha gave growth and yields. and produces the highest nitrogen uptake efficiency.